Socio-psychological features of the process of transformation of the social structure of society and the process of communication in the digital space - S. Grishaeva; O. Kulikova (Цифровая социология, 2019)
The article deals with such concepts as “offline environment” and “online status”. New types of migration processes in the digital space are revealed. The trends associated with stratification of society such as the transition from exclusion to inclusion and the impact of this transition to the educational space are outlined. As part of the impact of digital technologies on the social world, the changes that occur with the classical stratification criteria: income, power and profession are considered. In terms of income we are talking about such a concept as “cryptocurrency” (digital decentralized money); in terms of power the information society and the possibility of using false information to influence certain social processes, which makes the presence of formal power is not so effective, - are considered; in the part of the profession the huge mass of knowledge that is contained in the Internet and that the modern education system is not able to provide tools for navigation in this mass of knowledge, - are discussed. The main directions of changes in the cognitive and communicative aspects of communication, the negative consequences of the preference of the online environment to live communication and the impact on human mental activity, the development of addictive trends in communication by means of digital technologies, scenarios of conflict situations in the digital communication space and their impact on the social life of an individual are reviewed. Revealed the possible scenarios of the impact of the lack of non-verbal component and the critical thinking on coding and decoding of a particular information message.